(untitled) (Studia Prawnicze / The Legal Studies, 2009)
W doktrynie i orzecznictwie prawa karnego podkreślana jest szczególna wartość wykładni językowej. Z jej priorytetową rolą wiąże się wielkie nadzieje i oczekiwania W faworyzowaniu wykładni językowej upatruje się gwarancji dla realizacji zasady nullum crimen sine lege, twierdząc także, że prymat wykładni językowej jest prostą konsekwencją akceptacji wspomnianej zasady. Jednym z aspektów zasady nullum crimen sine lege, jest postulat określ oności przestępstwa, którego realizacja ma umożliwić adresatowi normy karnoprawnej odróżnienie czyny zabronionego od czynu nierelewantnego karnoprawnie, zaś organom stosującym prawo utrudnić arbitralne podejmowanie decyzji. O ile przed prawodawcą stawia się w związku z tym wymóg szczególnej precyzji „terminologicznej i logicznej ”, przejawiający się zwłaszcza w ograniczonym sięganiu po znamiona „ocenne”, o tyle na organach stosującymiprawo spoczywa z koli wymóg szczególnie restryktywnego przestrzegania obowiązujących reguł wykładni. „Rzeczywista” normatywna zawartość tekstu stanie się dla interpretatora dostępna, o ile będzie realizował określony paradygmat interpretacyjny, w którymi „rozstrzygające znaczenie dyrektyw językowych”, „pierwszeństwo wykładni literalnej”, „prymat wykładni językowej” stanowi zasadniczy element. Distinguishing the type of interpretation, in terms of directives in the process of judicial interpretation terms of directives, plays a primary role. So called triad-literal, systemic and purposive interpretation-seems to be a basic tool of a judge. The importance of the above mentioned distinction is even greater, if we take into consideration that this distinction is used to build models of preference: the model of priority of literal interpretation and the model of integrated interpretation. In the strategy of the priority of literal interpretation, commonly used by the judicature, the most important is the result, as a consequence of using literal interpretation. The interpreter should give the priority of using this land of interpretation in opposition to the other interpretational assumptions. The very high level of general wording of the literal directive should not procure greater concerns. Nevertheless some more strictly questions, show a lot of doubts. They impair inside conviction based on the belief, that literal interpretation is the best instrument to protect the legal certainty and substantiality of law. The paper consists of some different clues. In the first one, the authors consider the different meaning of literal interpretation and some preferences inside this interpretation. The goal is to show as much as possible ways of meaning of the «literal interpretation» .The next part presents the authors view on the specific and various meaning of the priority of literal interpretation. Last but not least, the authors try to find the answer on the question of the principle of the priority of legal interpretation, and some situations which condemn the above mentioned principle. The conclusion of this paper is based on the conviction, that the concept of the priority of the literal interpretation needs reformulation. The reality concluded in the reasons for the judgments, as well as the modern achievements in linguistic sciences, show that the language is illusive. Contrary to common expectations, the language could create unlimited possibilities for interpretation, rather than pointing out its boundaries.